(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2022)
Recurvature in tropical cyclones is not very uncommon, but rare. There are instances of recurved tropical cyclones forming over the Bay of Bengal. Some of them have hit the coastal regions of Bangladesh. In this research, the climatology and synoptic conditions of such events have been assessed. It has been found that 25 recurved tropical cyclones have hit Bangladesh throughout the period from 1891 to 2019. Most of them have occurred during the post-monsoon season. Again, there have been more cases of recurvature in tropical cyclones that hit the southwest coastal region of Bangladesh than the southeast. Although there are some differences between the direction and speed for the two coasts, but there are not much differences between them for their vector or scalar speeds. In addition, further assessment of the wind speeds and the intensities of tropical cyclones have revealed some interesting findings. The analyses of synoptic conditions for the recurved tropical cyclones have also obtained some important results. All these results and findings will aid in better forecasting of recurved tropical cyclones in the future. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(3), Special Issue 2022: 131-141